Small extracellular vesicles from human umbilical cord mesenchymal stem cells delivering miR-202-5p alleviate renal ischemia-reperfusion injury by targeting the GOLIM4/PI3K/AKT axis - Peng, Xiang; Shi, Wei; Yu, Haitao; Feng, Zhenwei; Wei, Zongjie; He, Weiyang; Gou, Xin; Xie, Yongpeng (Frontiers in Immunology, 2025)
BackgroundIschemia–reperfusion injury (IRI) is a leading contributor to acute kidney injury (AKI), resulting in severe renal dysfunction and increased mortality. Despite progress in medical research, effective therapies for IRI remain limited. Recently, small extracellular vesicles (sEVs) originating from human umbilical cord mesenchymal stem cells (HucMSC-sEVs) have gained attention as potential therapeutic agents for alleviating organ damage. This study aimed to investigate the protective effects of HucMSC-sEVs in renal IRI and explore the underlying mechanisms involved.MethodsHucMSC-sEVs were isolated from HucMSCs via differential ultracentrifugation. Their characteristics were analyzed via transmission electron microscopy (TEM), nanoFCM, and western blotting. The protective effects of HucMSC-sEVs on OGD/R-induced apoptosis in HK-2 cells were evaluated via western blotting and flow cytometric analysis. Additionally, to explore the molecular mechanisms, qRT-PCR, dual-luciferase reporter assays, and other techniques were employed to investigate the role of miR-202-5p in HucMSC-sEVs, with a focus on its ability to regulate the PI3K/AKT pathway through the targeting of GOLIM4. Finally, the therapeutic effects of HucMSC-sEVs were evaluated in vivo via a mouse model of IRI.ResultsThe HucMSC-sEVs exhibited a characteristic biconcave circular morphology, with a particle size range of 60–100 nm and an average diameter of 79.8 nm. Western blotting confirmed the presence of sEV markers CD9 and TSG101, and HucMSC-sEVs were efficiently taken up by HK-2 cells. In the OGD/R model, HucMSC-sEVs significantly reduced apoptosis, attenuated the expression of BAX and CC3, and promoted the upregulation of BCL-2. Mechanistic studies revealed that HucMSC-sEVs deliver miR-202-5p, which targets GOLIM4 and activates the PI3K/AKT pathway, ultimately reducing renal tubular cell apoptosis. In the mouse IRI model, HucMSC-sEVs significantly alleviated kidney damage and reduced the serum creatinine and urea nitrogen levels.ConclusionThis study is the first to demonstrate the role of HucMSC-sEVs in attenuating renal IRI both in vitro and in vivo through the modulation of the GOLIM4/PI3K/AKT pathway via miR-202-5p. These findings identify a novel molecular target for the treatment of AKI via HucMSC-sEVs and provide a strong theoretical basis for their potential clinical application.